1962
DOI: 10.1002/jctb.5010120302
|View full text |Cite
|
Sign up to set email alerts
|

One‐step catalytic conversion of ethanol to butadiene in the fixed bed. II BINARY‐ AND TERNARY‐OXIDE CATALYSTS

Abstract: The activity of a large number of binary-and ternary-oxide catalyst systems comprising dchydrating and dehydrogenating components has been tested for the conversion of ethanol to butadiene in the fixed bed.-Alumina-zinc oxide (60 : 40) was the best catalyst, and it gave a maximum of 55.8% process yield of ethanol to butadiene a t a temperature of 425" and ethanol feed rate of 1.875 ml./h./g. of catalyst.Other promising binary catalysts are alumina-magnesium oxide (80 : 20), alumina-ferric oxide or -chromium ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 2 publications
0
30
0
Order By: Relevance
“…As the activity of Cr/MCM-41 was not reported, it is difficult to the role of barium in this improvement or if Ba and Cr had any synergic contribution in that regard. It should be noted that chromium-containing amphoteric mixed oxides were reported as active for the ETB reaction, but not silica-supported Cr 2 O 3 , evidencing some contribution from MCM-41 and/or Ba [26,41]. A decrease in ethanol conversion is observed over a period of 24 h. Coke formation on the catalytic surface, evidenced by thermal gravimetric analysis, is the likely cause of this deactivation.…”
Section: Other Catalytic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the activity of Cr/MCM-41 was not reported, it is difficult to the role of barium in this improvement or if Ba and Cr had any synergic contribution in that regard. It should be noted that chromium-containing amphoteric mixed oxides were reported as active for the ETB reaction, but not silica-supported Cr 2 O 3 , evidencing some contribution from MCM-41 and/or Ba [26,41]. A decrease in ethanol conversion is observed over a period of 24 h. Coke formation on the catalytic surface, evidenced by thermal gravimetric analysis, is the likely cause of this deactivation.…”
Section: Other Catalytic Systemsmentioning
confidence: 99%
“…Mixed oxides with either acid, basic and/or redox properties are a significant category of those. Bhattacharyya et al have thoroughly investigated the potential of binary and ternary metal oxide systems and discovered that a mixture of amphoteric alumina with basic and redox zinc oxide (Al2O3-ZnO (60:40)), is the most active catalyst (see Table 1) [26]. Other good catalysts included the mixture of alumina with basic magnesia or alumina with chromium oxide possessing redox properties.…”
Section: Catalyst Designmentioning
confidence: 99%
“…As reported in former literatures, 8,9 MgO-SiO 2 and ZrO 2 -SiO 2 were regarded as the two most promising catalytic system in ethanol to BD process, each for one-step and two-step, respectively. Dozens of studies were performed on MgO-SiO 2 catalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, reaction variables are investigated using the "change-one-factor-at-atime" method; that is, one variable is changed while the other experimental conditions are kept constant [2,10,12,13,26,27,[29][30][31]. Based on this method, it has been found that temperature exerts an important nonlinear effect on 1,3-BD yields, as observed with help of different catalysts [13,19,26,30,31]. Similar studies have shown that the weight hourly space velocity (WHSV) also modifies 1,3-BD yields and selectivities [2,13,19,26,27,30,31].…”
Section: Introductionmentioning
confidence: 99%